The impact of frequency on the performance of microwave ablation. (2nd January 2017) - Sawicki, James F.; Shea, Jacob D.; Behdad, Nader; Hagness, Susan C.
Abstract: Purpose: The use of higher frequencies in percutaneous microwave ablation (MWA) may offer compelling interstitial antenna design advantages over the 915 MHz and 2.45 GHz frequencies typically employed in current systems. To evaluate the impact of higher frequencies on ablation performance, we conducted a comprehensive computational and experimental study of microwave absorption and tissue heating as a function of frequency. Methods: We performed electromagnetic and thermal simulations of MWA in ex vivo and in vivo porcine muscle at discrete frequencies in the 1.9–26 GHz range. Ex vivo ablation experiments were performed in the 1.9–18 GHz range. We tracked the size of the ablation zone across frequency for constant input power and ablation duration. Further, we conducted simulations to investigate antenna feed line heating as a function of frequency, input power, and cable diameter. Results: As the frequency was increased from 1.9 to 26 GHz the resulting ablation zone dimensions decreased in the longitudinal direction while remaining relatively constant in the radial direction; thus at higher frequencies the overall ablation zone was more spherical. However, cable heating at higher frequencies became more problematic for smaller diameter cables at constant input power. Conclusion: Comparably sized ablation zones are achievable well above 1.9 GHz, despite increasingly localised power absorption. Specific absorption rate alone does not accurately predict ablation performance, particularly at higher frequencies where thermal diffusion plays an important role. Cable heating due to ohmic losses at higher frequencies may be controlled through judicious choices of input power and cable diameter.